PENINGKATAN KEMAMPUAN MEMBACA PESERTA DIDIK MELALUI MEDIA PERMAINAN KARTU HURUF DI MI DARUS SHOLIHIN - Karimah, Uqdatul; Khosiah, Nur (LPPM STAI Muhammadiyah Probolinggo, 2024)
Education is something that must be obtained by all Indonesian citizens without exception from the lower classes to the upper middle classes, for this reason the government requires twelve years of study or up to high school. This is in accordance with the educational goals of the Indonesian nation as stated in paragraph 4 of the 1945 Constitution. As educators, we must be able to adapt to the times and do the best for our students, especially those at the elementary school level. The aim of this research is to improve the reading skills of grade 1 students at MI. Darus Sholihin, Boto Village, Lumbang District, Probolinggo Regency using PTK research (Classroom Action Research). Data collection techniques used observation, interview and documentation methods. The results of this study showed that between cycle 1, among others, children's accuracy in playing letter cards was 68.05%, children's accuracy in sorting the alphabet was 64.02% and children's ability to arrange letters into sentences was 67.01%, while in cycle 2, children's accuracy in playing letter cards was 97.01%, children's accuracy in sorting the alphabet was 95.07% and children's ability to arrange letters into sentences was 98.05%. So there was an increase between cycle 1 to cycle 2 using the Letter Card Game Media.